A bibliometric and scientific knowledge-map study of the chimeric antigen receptor (CAR) natural killer (NK) cell-related research from 2010 to 2022 - Zhang, Juan; Chen, Peng; Miao, Lele (Frontiers in Immunology, 2022)
Objectives As emerging adoptive immunotherapy after CAR-T cell therapy, CAR-NK cell therapy has been developing rapidly in recent years. Presently, the research on CAR-NK cells has become a hotspot in the field of tumor immunotherapy. Methods In this descriptive study, CtieSpace and VOSviewer were used to perform the bibliometric and scientific knowledge-map analysis of articles and reviews related to CAR-NK cells. Results 5371 authors from 715 institutions in 65 countries published 1028 papers about CAR-NK cells in 346 journals. The number of publications related to CAR-NK cells was increasing overall, especially from 2018 to 2021. The United States was in a leading position. The most active institution was Univ Texas, MD Anderson Cancer Center (USA). The journal with the most publications was Frontiers in immunology, and the most co-cited journal was Blood. The researcher with the most published papers was Winfried S. Wels, while the most co-cited researcher was Shannon L Maude. The research of CAR-NK cells in hematological malignancies and solid tumors (especially the selection of targets and the evaluation of efficacy and safety) was a research hotspot in this field. The emerging topics mainly included three aspects. First, further improve the proliferation and persistence of NK cells in vivo. Secondly, optimizing and improving the CAR structure for NK cells to improve the anti-tumor ability of CAR-NK cells. Thirdly, the related research of CRISPR/Cas9 gene-editing technology in constructing engineered immune cells. Conclusion In this study, a bibliometric and scientific knowledge-map study provided a unique and objective perspective for the CAR-NK cell field. This information would provide a helpful reference for researchers interested in this field.